Social Policy and Development Centre. Social Development in Pakistan: Annual Review 1999. Karachi. Social Policy and Development Centre and Oxford University Press. 1999. Pakistan Rs 395/(Pb). 166 pages. (The Pakistan Development Review, 1999)
This Report on Social Development in Pakistan is a welcome addition to the economic literature on Pakistan; it reviews the development and policies during the past year (1999) in the perspective of long-run trends. The 1999 issue has been enriched by an analysis of the impact of economic sanctions on Pakistan's economy. The five chapters of the Report discuss crises in the economy focussing on short- and long-run problems, the impact of the economic sanctions, the IMF package, and, alternative strategies of economic and social development, the future outlook for social development in Pakistan, the Social Action Programme and Social Safety "Nets. Data and important social events during the year are presented in the annexures.